Handbook on Analyzing Human Genetic Data Computational Approaches and Software - Lin, Shili; Zhao, Hongyu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The discipline of statistical genetics is highly computational. Be it exact computational methods, simulation based, or a hybrid of the two, computational packages are indispensable tools and constant companions of researchers in the field. This handbook is intended to provide human geneticists and other biomedical researchers with guidance on selections of appropriate computational methods and software packages for their specific genetic problems. It may also be used by students and other learners as a reference in conjunction with a more theoretical and/or methodologically oriented text book. This book tries to strike a balance between methodological expositions and practical guidelines for software selections. Wherever possible, comparisons among competing methods and software are made to highlight the relative advantages and disadvantage of the approaches so that the readers can make informed choices to best match their specific needs.
Population Genetics -- Haplotype Structure -- Linkage Analysis of Qualitative Traits -- Linkage Analysis of Quantitative Traits -- Markov Chain Monte Carlo Linkage Analysis Methods -- Population-Based Association Studies -- Family-Based Association Studies -- Haplotype Association Analysis -- Multiple Comparisons/Testing Issues -- Estimating the Absolute Risk of Disease Associated with Identified Mutations -- Processing Large-Scale, High-Dimension Genetic and Gene Expression Data.
Keywords: Medicine; Human genetics; Bioinformatics; Genetics -- Mathematics; Mathematical statistics; Statistics; Biomedicine; Human Genetics; Statistics for Life Sciences, Medicine, Health Sciences; Bioinformatics; Computational Biology/Bioinformatics.; Genetics and Population Dynamics; Statistical Theory and Methods